Weed interference on coffee fruit production during a four-year investigation after planting - Lemes, L. N. [UNESP]; Carvalho, L. B. [UNESP]; Souza, M. C. [UNESP]; Alves, P. L.C.A. [UNESP] (My University, 2010)
Aiming to investigate the effects of crescent weedy periods on the extension of the period before weed interference on coffee fruit production under two kinds of weed control, field trials were conducted in Arceburgo-MG, Brazil, during the period 2000 - 2004. Two groups of treatments were established according to the kind of weed control: (i) total area control and (ii) 0.5 m strip control at each side of planting line. Six periods of weed coexistence were established in both groups, at the beginning of the rainy season: 0, 30, 60, 90, 120 and 150 days. At the end of each period, weeds were monthly removed by glyphosate applications until coffee harvest. Main weeds found during investigation were Alternanthera tenella, Amaranthus hybridus, Commelina benghalensis, Digitaria horizontalis, Digitaria insularis, Parthenium hysterophorus and Euphorbia heterophylla. Weed density and dry matter varied among periods of coexistence and between kinds of control throughout the full time investigations, so that it was not possible to establish any correlation between their evaluations. Period before weed interference was higher in 2001/2002 than in 2002/2003 and 2003/2004, suggesting that the weed management adopted in 2000/2001 was not enough to prevent weed interference throughout the investigation, in both total and strip control. © 2010 Academic Journals.
Keywords: Coffea arabica; Competition; Glyphosate; Weed management; Weedy periods